Antimalarial activity of new acridinone derivatives - Fernández Calienes, Aymé (2011)
Malaria is one of the major threats concerning world public health. Resistance to the current antimalarial drugs has led to searches for new antimalarial compounds. Acridinone derivatives have recently demonstrated to be active against malaria parasite. We focused our attention on synthesized new acridinone derivatives, some of them resulting with high antiviral and trypanocidal activity. In this study new derivatives of 10-alyl-, 10-(3-methyl-2-butenyl)- and 10-(1,2-propadienyl)-9(10H)-acridinone were evaluated for their antimalarial activity against Plasmodium falciparum. To assess the selectivity, cytotoxicity was assessed in parallel against human MRC-5 cells. Inhibition of β-hematin formation was determined using a spectrophotometric assay. Mitochondrial bc 1 complexes were isolated from yeast and bovine heart cells to test acridinone inhibitory activity. This study resulted in the identification of three compounds with submicromolar efficacy against P. falciparum and without cytotoxic effects on human cellular line. One compound, IIa (1-fluoro-10-(3-methyl-2-butenyl)-9(10H)-acridinone), can be classified as hit for antimalarial drug development exhibiting IC 50 less than 0.2μg/mL with SI greater than 100. In molecular tests, no relevant inhibitory activity was obtained for our compounds. The mechanism of acridinones antimalarial action remains unclear.